Conceptual framework of modern cellular network cybersecurity rising - Одарченко, Роман Сергійович; Гнатюк, Віктор Олександрович (Ukrainian Scientific Journal of Information Security, 2016)
This paper analyzes the evolution of mobile networks from 1st to 5th generations. In addition, analyzed security of these networks was also examined their evolution. More details were discussed possible technical solutions for the most advanced security systems currently LTE Networks. As a result of the research it became clear that the 5G network will play in the future, the most important role in the formation of e-society used to meet the needs and requirements of critical infrastructure and so on. On the basis of the research was proposed concept of cellular networks cybersecurity systems building, while outlining key areas of improvement of modern systems of security, identity management, security, network, energy efficiency, flexible and scalable architecture, security, cloud services and more. This will create a new more flexible scalable security architecture of cellular networks, which will be able to provide all the requirements of a variety of disparate systems within the scope of this type of network, including the 5th generation. There were also proposed technical improvements to the architecture and technology of LTE cellular networks in view of the latest developments in this field.